Increasing groundwater replenishment through environmentally friendly parking lot pavement model. Issue 1 (January 2022) - Wulandari, D A; Suripin,; Ulfiana, D; Hermawan, C W; Grimaldi, E
Abstract: Paving blocks are basically permeable pavements, which can reduce surface runoff by infiltrate rainwater into the ground. So that the installation of paving blocks on parking lots has an environmental function for filling groundwater. However, what is happening in the field today is that paving blocks behave like an impermeable layer. When it rains, it cannot absorb water or only absorbs a little water so that inundations occur. This can be caused by, among other things, the installation of paving blocks or the improper pavement structure. Therefore, it is necessary to develop a model of the parking lot pavement structure that is environmentally friendly, while contributing to groundwater filling, and reducing the surface runoff. The research was conducted by making a physical model of the permeability test. Parking lot pavement structure with arrangement permeable paving block, bedding layer and graded based layer will be placed on a test kit equipped with a control valve. With the system of partly filtration, it will be possible to know the amount of discharge absorbed by the model. So that the parking lot pavement structure will be obtained that can contribute to groundwater filling and its application to various types of subgrade.